Dietary diversity among women in the reproductive age group in a rural field practice area of a medical college in Mandya district, Karnataka, India - SK, Shashikantha; MP, Sheethal; BK, Vishma (International Journal Of Community Medicine And Public Health, 2017)
Background: Micronutrient malnutrition remains one of the largest nutritional problems worldwide. Monotonous diets based on starchy staples lack essential micronutrients and contribute to the burden of malnutrition and micronutrient deficiencies. Intake of diverse diet is a cost-effective strategy to overcome this problem. The objective of the study was to assess the dietary diversity among women in reproductive age group in a rural field practice area and to determine the nutritional status of the women in the reproductive age group. Methods:A cross-sectional study was conducted for a period of 3months in the rural area. Women in reproductive age group were included in the present study. A pretested questionnaire was used to obtain the information regarding their socio-demographic profile and food consumed. Dietary diversity score was measured using the food and agricultural organization (FAO) guidelines. Weight, height and waist circumference of the participants were measured to determine their nutritional status. Results: The mean age of the study subjects was 33.68±9.27 years. Majority of them had dietary diversity score (DDS) and food variety score (FVS) score above 5 and 4 respectively. Mean BMI was 23.26±4.31 kg/mt2.Fifty percent of them had a Normal BMI range. One third (28.6% ±6.5%) of them were malnourished. The mean waist circumference was 79.31±10.58cms. On application of logistic regression, those aged between 15-30 years had better odds of having DDS of 5 and above (aOR 2.348 CI 0.743-7.424). Subjects with normal BMI range also had better odds of having DDS of 5 and above (aOR 0.861 CI 0.154-4.799). Conclusions:The study found most of the women in the reproductive age group were consuming a diverse diet and those subjects with better dietary diversity score had their body mass index in the normal range.